Transforming growth factor-β: an important mediator in Helicobacter pylori-associated pathogenesis - Shuang, Li N.; chuan, Xie; hua, Lu n. (Frontiers in Cellular and Infection Microbiology, 2015)
Helicobacter pylori (H.pylori) is a Gram-negative, microaerophilic, helical bacillus that specifically colonizes the gastric mucosa. The interaction of virulence factors, host genetic factors, and environmental factors contributes to the pathogenesis of H. pylori-associated conditions, such as atrophic gastritis and intestinal metaplasia. Infection with H. pylori has recently been recognized as the strongest risk factor for gastric cancer. As a pleiotropic cytokine, transforming growth factor (TGF)-β regulates various biological processes, including cell cycle, proliferation, apoptosis, and metastasis. Recent studies have shed new light on the involvement of TGF-β signaling in the pathogenesis of H. pylori infection. This review focuses on the potential etiological roles of TGF-β in H. pylori-mediated gastric pathogenesis.